The expanding domain of strategic management research and the quest for integration - Durand, Rodolphe; Grant, Robert M.; Madsen, Tammy L. (Strategic Management Journal, 2017)
Research summary : This special issue of Strategic Management Journal was motivated by concern that the growing scope and diversity of the strategic management field creates the risk of incoherence and fragmentation and the belief that research reviews could contribute to synthesis and integration. In this introductory essay, we address the expanding domain of strategic management, consider where its boundaries lie, identify the forces engendering fragmentation, and discuss how this special issue—and research reviews in general—can assist convergence within the field of strategy. We conclude by addressing the potential for integration more broadly in relation to the theories we deploy, the phenomena we investigate, and cohesiveness of our scholarly community . Managerial summary : The expanding domain of strategic management reflects the widening range of strategic issues that practising managers face. However, the fragmentation that has accompanied this broadening scope impedes the usefulness of strategic management research in guiding strategic decision making. We argue that reviews of strategic management research, such as those included within this special issue, can support the accumulation of an integrated, empirically-validated knowledge base which is essential to informing management practice . Copyright © 2016 John Wiley & Sons, Ltd.